Isu Etika dalam Sistem Manajemen Pembiayaan Pendidikan di Sekolah Dasar: Pertimbangan dan Solusi: Ethical Issues in the Educational Financing Management System in Elementary Schools: Considerations and Solutions - Muslikhin, Muslikhin; Khoeruddin, Liana Ariesha (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This study delves into ethical concerns within educational financing management systems, emphasizing considerations and solutions. Ethical management of education funds is deemed crucial for transparent, accountable, and morally sound fund utilization. The investigation incorporates an analysis of pertinent domestic journal articles and books, identifying ethical issues related to fund allocation, transparency, accountability, conflicts of interest, and social responsibility in education financing. Cases, research, and expert perspectives, contextualized within Indonesia, are presented for each issue. Furthermore, the study proposes solutions applicable to educational institutions like schools, universities, and governments to enhance ethical practices in fund management. Recommendations include heightened transparency, integration of ethics education into curricula, staff and teacher training, development of codes of ethics, parental involvement, partnerships with relevant organizations, and continuous monitoring of ethical practices. The research outcomes offer valuable insights into the significance of ethics in education funding management, delineating various measures to fortify ethical practices in the educational realm. Practical implications and recommendations for on going enhancement in education funding management are also discussed.